2020
DOI: 10.1136/gutjnl-2019-319726
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the gut microbial signature driving the efficacy of prebiotic intervention in obese patients

Abstract: ObjectiveThe gut microbiota has been proposed as an interesting therapeutic target for metabolic disorders. Inulin as a prebiotic has been shown to lessen obesity and related diseases. The aim of the current study was to investigate whether preintervention gut microbiota characteristics determine the physiological response to inulin.DesignThe stools from four obese donors differing by microbial diversity and composition were sampled before the dietary intervention and inoculated to antibiotic-pretreated mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 41 publications
6
129
0
Order By: Relevance
“…Recently, Xia et al negatively correlated Proteobacteria, Butyricimonas, Parabacteroides, and Bilophila abundance with liver inflammation and intestinal epithelial claudin expression [33]. Moreover, Victivallis and Butyricimonas abundance have been positively correlated with hepatic lipid accumulation [34]. Altogether, this evidence suggests that the intestinal microbiome profile of rats fed high dietary magnesium could be potentially more pathogenic and pro-inflammatory than those from the C-Mg or L-Mg group.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Xia et al negatively correlated Proteobacteria, Butyricimonas, Parabacteroides, and Bilophila abundance with liver inflammation and intestinal epithelial claudin expression [33]. Moreover, Victivallis and Butyricimonas abundance have been positively correlated with hepatic lipid accumulation [34]. Altogether, this evidence suggests that the intestinal microbiome profile of rats fed high dietary magnesium could be potentially more pathogenic and pro-inflammatory than those from the C-Mg or L-Mg group.…”
Section: Discussionmentioning
confidence: 95%
“…He et al (2017) suggested that short‐chain inulin did not have a profound gut protective effect as well as long‐chain inulin, implying the type and chain length of inulin, is important for its physiological functions. The physiological characteristics of experimental animals also affect the efficacy of inulin intervention in different animals (Rodriguez et al., 2020). Loh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bifidobacterium did not covary with this component, the Bifidobacterium intake might have indirectly affected DMN connectivity in stress, potentially via modulation of the abundance of Ruminococcus 2 and Blautia. Indeed, the pre-existing levels of Blautia and Ruminococcae correlated with the metabolic outcomes of a Bifidobacterium-targeting prebiotic intervention in obese patients (40). Furthermore, Blautia has been found to be the only genus to be enriched in depressionmodel rats (41) and both Blautia and Ruminococcae correlated with stress-related depression-like behaviour in mice (42).…”
Section: Discussionmentioning
confidence: 99%